A new gene inventory of the ubiquitin and ubiquitin-like conjugation pathways in giardia intestinalis (2020)
BACKGROUND Ubiquitin (Ub) and Ub-like proteins (Ub-L) are critical regulators of complex cellular processes such as the cell cycle, DNA repair, transcription, chromatin remodeling, signal translation, and protein degradation. Giardia intestinalis possesses an experimentally proven Ub-conjugation system; however, a limited number of enzymes involved in this process were identified using basic local alignment search tool (BLAST). This is due to the limitations of BLAST’s ability to identify homologous functional regions when similarity between the sequences dips to < 30%. In addition Ub-Ls and their conjugating enzymes have not been fully elucidated in Giardia. OBJETIVE To identify the enzymes involved in the Ub and Ub-Ls conjugation processes using intelligent systems based on the hidden Markov models (HMMs). METHODS We performed an HMM search of functional Pfam domains found in the key enzymes of these pathways in Giardia’s proteome. Each open reading frame identified was analysed by sequence homology, domain architecture, and transcription levels. FINDINGS We identified 118 genes, 106 of which corresponded to the ubiquitination process (Ub, E1, E2, E3, and DUB enzymes). The E3 ligase group was the largest group with 82 members; 71 of which harbored a characteristic RING domain. Four Ub-Ls were identified and the conjugation enzymes for NEDD8 and URM1 were described for first time. The 3D model for Ub-Ls displayed the β-grasp fold typical. Furthermore, our sequence analysis for the corresponding activating enzymes detected the essential motifs required for conjugation. MAIN CONCLUSIONS Our findings highlight the complexity of Giardia’s Ub-conjugation system, which is drastically different from that previously reported, and provides evidence for the presence of NEDDylation and URMylation enzymes in the genome and transcriptome of G. intestinalis.